Effect of dietary nano α-tocopherol acetate plus selenium on productivity, immune status, intestinal morphometry and carcass traits of broiler chicken - Abdulameer, Yahya; Ajafar, Majeed; Rabee, Raed (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: Nano-vitamins and minerals are used in animal nutrition to improve performance and health of broiler chickens as a potential alternative to antibiotic growth promoters. Objective: To evaluate the effect of several levels of a dietary nano α-tocopherol acetate plus selenium compound (NTS) on growth, intestinal histomorphometry, carcass traits, and immune status of broiler chickens. Methods: A total of 240 one-day-old Ross 308 chickens were randomly divided into four groups, each one with three pens (n=20 per pen). Four doses of nano α-tocopherol acetate and selenium (0, 5, 7, and 10 mg/kg) were included in the basal diet for 42 days. Results: Final body weight, cumulative body weight gain, and final conversion ratio significantly improved with increasing NTS levels (p<0.05). Carcass traits and weight of internal organs increased in the groups fed 7 and 10 mg/kg NTS. High NTS doses significantly increased immune vaccine titers against Newcastle disease, avian influenza virus, infectious bursal disease, and infectious bronchitis. Moreover, dietary addition of NTS improved intestinal morphometry. Conclusion: Thus, NTS (7 and 10 mg/kg) can be added to poultry rations to improve production, carcass characteristics, and immune status of broilers. Further studies are needed to evaluate NTS residues in meat.